(untitled) (Journal of Pharmaceutical Negative Results, 2021)
BACKGROUND: The occurrence of thyroid dysfunction in pregnancy poses tremendous risks to the mother and fetus. Accurate knowledge of the frequency and implications of thyroid disorders during pregnancy is important for proper management and prevention of ill effects. Objectives: To determine the prevalence of thyroid dysfunction among pregnant women who had never been diagnosed with any previous thyroid diseases. Study Design: A Cross Sectional Study Place and Duration of Study: Department of Endocrinology HMC Peshawar from 05-jan-2021 to 05-july-2021 METHODS: The study used a cross-sectional design, conducted at the Department of Endocrinology, HMC Peshawar A total sample size of 150 pregnant women without prior thyroid diseases was selected for this study who underwent thyroid function tests including serum levels of TSH and FT4. Thyroid dysfunction was evaluated through TSH levels in blood serum samples collected from subjects. Statistical analysis was done using descriptive statistics (numbers %) while inferential statistics were used test associations between maternal characteristics and Prevalence (Chi-square test). A comprehensive approach which aimed at ascertaining the status on thyroids during pregnancy in Peshawar region. RESULTS: A total number of one hundred and fifty pregnant females without any known predisposing factors affecting their thyroid functions were involved in this study. Among these individuals, abnormal TSH levels indicative of abnormality in functioning ranged from hypothyroidism to hyperthyroidism, occurred in just a quarter (25%) [9]. Out all those cases that had indicated an increase in their TSH values by having higher concentrations than normal standards, only some showed quite less drastic changes while majority seemed not to experience such change at all since over half indicated suppressed levels thus causing what they could have called it as overt subclinical hyperthyroidism.Moreover,no significant number of patients(75%) which was still within the range. A higher prevalence of abnormal TSH level in women aged 35 years and above as compare to those less than this age with 35% having thyroid dysfunction. Also, there is parous showing that primipara had more number of those affected by thyroid dysfunctions (30%) when compared multipara (20%). The third significant factor was BMI which showed effect on thyroid status during pregnancy. Women with a BMI ≥ 25 kg/m² were noted to record a greater percentage of thyroids problems at 30%, whereas among the normal population only 20% were observed to have the same condition.Moreover, gestational age at the time of assessment has been found as significant factors influencing the occurrence of thyroid diseases during pregnancy where women assessed in second trimester had reduced prevalence at 20%. CONCLUSION: The thyroid dysfunction for pregnant females without prior thyroid illness indicated considerable rates in Peshawar area.